Regional hippocampal involvement and cognitive impairment in pediatric multiple sclerosis. (April 2016) - Rocca, Maria A; Morelli, Maria E; Amato, Maria P; Moiola, Lucia; Ghezzi, Angelo; Veggiotti, Pierangelo; Capra, Ruggero; Pagani, Elisabetta; Portaccio, Emilio; Fiorino, Agnese; Pippolo, Lorena; Pera, Maria C; et al.
Objectives: We assessed global and regional hippocampal volume abnormalities in pediatric multiple sclerosis (MS) patients and their correlations with clinical, neuropsychological and magnetic resonance imaging metrics. Methods: From 53 pediatric MS patients and 18 healthy controls, global hippocampal volume was computed using a manual tracing procedure. Regional hippocampal volume modifications were assessed using a radial mapping analysis. MS patients with abnormal performance in three or more tests of a neuropsychological battery for children were classified as cognitively impaired. Results: Global hippocampal volume was reduced in MS patients compared with controls, but did not correlate with clinical, neuropsychological and magnetic resonance imaging measures. Compared to controls, MS patients experienced bilateral radial atrophy of the cornu ammonis, subiculum and dentate gyrus subfields as well as radial hypertrophy of the dentate gyrus subfield. Regional hippocampal volume modifications correlated with brain T2 lesion volume as well as attention and language abilities. Global hippocampal volume did not differ between cognitively impaired ( n =12) and cognitively preserved MS patients. Compared to cognitively preserved, cognitively impaired MS patients had atrophy of the subiculum and dentate gyrus subfields of the right hippocampus. Conclusions: Hippocampal subregions have different vulnerability to damage in pediatric MS. Regional rather than global hippocampal involvement contributes to global cognitive impairment as well as to deficits of selected cognitive tests.